The action of Vitamin C in the coagulation process: an experimental in vitro study - Macedo, Ana Alves; Oliveira, Beatriz Guitton Renaud Baptista de; Kang, Hye Chung; Carvalho, Magali Rezende de (Online Brazilian Journal of Nursing, 2010)
Vitamin C is empirically used by nurses to unblock long-term venous catheters. The study aims at analyzing the action of vitamin C in the coagulation process, establishing an in vitro coagulation model and fibrinolysis. It is an in vitro experimental study of the total blood of 10 healthy volunteers and 13 pools of citrated plasma. The results showed reduction of serum D-dimer with statistical significance when treated with vitamin C before and after clot formation. The weight of clots in blood presented significant reduction only when treated with vitamin C before the clotting process. However, when using vitamin C after clot formation a change is noticed in its structure and consistency. There were no significant differences in the weight of fibrin clots. It was concluded that vitamin C acts with greater intensity during the pre-clot formation phase and with less intensity in the two subsequent hours.